Diagnostic utility of neurogenic biomarkers in differentiating sepsis with and without associated encephalopathy: a systematic review and meta-analytic approach - Lin, Xiaofei; Zhang, Jun; Ren, Tailiang; Cao, Haixia; Chang, Cheng; Wang, Yumei (Frontiers in Neurology, 2025)
BackgroundSepsis-associated encephalopathy (SAE) is a frequent complication of sepsis, manifesting as acute brain dysfunction and often resulting in persistent cognitive deficits, neurological impairment, and increased mortality. Timely and accurate diagnosis of SAE is essential to guide therapeutic decisions and improve clinical outcomes. In recent years, neurogenic biomarkers have emerged as potential serum-based indicators for the diagnosis and progression monitoring of SAE.MethodsA comprehensive search of PubMed/MEDLINE, Embase, the Cochrane Library, Web of Science, and Scopus was conducted from inception to 30 April 2025. Weighted mean differences (WMDs) and 95% confidence intervals (CIs) were calculated using a random-effects model.ResultsForty-seven studies (50 arms) were included. Random-effects analysis revealed significant differences in serum NSE levels between SAE and NE adult patients (WMD = 6.82; 95% CI: 5.43, 8.21; P < 0.001), S100β levels (WMD = 0.48; 95% CI: 0.37, 0.60; P < 0.001), GFAP levels in the SAE group (WMD = 62.28; 95% CI: 45.42, 79.14; P < 0.001), TAU levels in the SAE individuals (WMD = 1.73; 95% CI: 0.95, 2.51; P < 0.001), UCH-L1 levels in SAE patients (WMD = 1.73; 95% CI: 0.95, 2.51; P < 0.001), APACHE II scores in the SAE group (WMD = 6.30; 95% CI: 4.61, 7.99; P < 0.001), and SOFA scores in SAE (WMD = 3.65; 95% CI: 2.96, 4.34; P < 0.001).ConclusionElevated serum levels of neurogenic biomarkers may serve as potential predictors of SAE and are associated with increased mortality in septic patients. These biomarkers show promise as reliable, minimally invasive tools for diagnosis and longitudinal monitoring of SAE. However, these findings should be interpreted with caution due to substantial heterogeneity across the included studies.